2010
DOI: 10.1038/ejhg.2010.95
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide gene expression profiling of the Angelman syndrome mice with Ube3a mutation

Abstract: Angelman syndrome (AS) is a human neurological disorder caused by lack of maternal UBE3A expression in the brain. UBE3A is known to function as both an ubiquitin-protein ligase (E3) and a coactivator for steroid receptors. Many ubiquitin targets, as well as interacting partners, of UBE3A have been identified. However, the pathogenesis of AS, and how deficiency of maternal UBE3A can upset cellular homeostasis, remains vague. In this study, we performed a genome-wide microarray analysis on the maternal Ube3a-def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 34 publications
2
22
1
Order By: Relevance
“…3D). It was also reported that Sst transcription was down-regulated in the Ube3a mÀ/p+ cerebellum compared to wild-type mice [26]. Taken together, these data suggest that E6AP can function as a coactivator for the MeCP2-mediated regulation of Sst expression in vivo.…”
Section: E6ap Cooperates With Mecp2 To Regulate Target Gene Expressionsupporting
confidence: 61%
See 1 more Smart Citation
“…3D). It was also reported that Sst transcription was down-regulated in the Ube3a mÀ/p+ cerebellum compared to wild-type mice [26]. Taken together, these data suggest that E6AP can function as a coactivator for the MeCP2-mediated regulation of Sst expression in vivo.…”
Section: E6ap Cooperates With Mecp2 To Regulate Target Gene Expressionsupporting
confidence: 61%
“…We next asked whether MeCP2 and E6AP could function together in regulating target gene expression, given that MeCP2 and E6AP both act as regulators of gene expression independently [10,17,26,27]. Since E6AP can act as a transcriptional coactivator [17], we tested whether E6AP acts as a coactivator for MeCP2.…”
Section: E6ap Cooperates With Mecp2 To Regulate Target Gene Expressionmentioning
confidence: 99%
“…These results show that miRNA levels detected by microarray are reliable and can be used for the further analysis. Identification of 20 miRNAs associated with survival in the training set The microarray raw data in the training set were normalized and transformed into a log 2 ratio of hepatocellular carcinoma to noncancerous liver by BRB-ArrayTools and then miRNAs with expression in less than 15% of samples and change in expression less than 1.5-fold were filtered (23,24). To identify a miRNA signature correlated with patients' survival, the relationship between miRNA expression levels and patients' survival was assessed in the training set by fitting Cox proportional hazards models using BRBArrayTools software and miRNAs were chosen by the criteria of P < 0.1.…”
Section: Resultsmentioning
confidence: 99%
“…These genes are functioning in signal transduction, nervous system development and cell death. Some of those genes (Fgf7, Glra1, Mc1r, Nr4a2, Slc5a7 and Epha6) are confirmed of relevant with AS phenotype [49]. It was also shown that elevated Arc level in AS mouse disturbs the brain-derived neurotrophic factor (BDNF) to recruit the postsynaptic density-95 (PSD-95) protein, disrupts association of PSD-95 with TrkB, and the association of PLCγ and Grb2-associated binder 1 (Gab1) with TrkB, therefore impairing BDNF, TrkB and PI3K-Akt pathways [57].…”
Section: Pathophysiological and Molecular Changesmentioning
confidence: 87%
“…It was reported that the post mitotic neonatal neurons are decreased after maternal Ube3a inactivation in AS mouse hippocampus [48]. The loss of neurons may be due to either impaired metabolism or the disturbance of genes involved in cell death process [49], or both. It was also shown that mitochondria in AS mouse exhibited a smaller size in the hippocampus and a partial oxidative phosphorylation defect in the whole brain [22].…”
Section: Pathophysiological and Molecular Changesmentioning
confidence: 99%